1998
DOI: 10.1021/bi971032a
|View full text |Cite
|
Sign up to set email alerts
|

Conformational States in Denaturants of Cytochrome c and Horseradish Peroxidases Examined by Fluorescence and Circular Dichroism

Abstract: Steady-state fluorescence and circular dichroism (CD) were used to examine the unfolding in denaturants of recombinant cytochrome c peroxidase [CCP(MI)] and horseradish peroxidase (HRP) in their ferric forms. CCP(MI) unfolds in urea and in guanidine hydrochloride (GdHCl) at pH 7.0, while HRP loses its secondary structure only in the presence of GdHCl. CCP(MI) unfolds in urea by two distinct steps as monitored by fluorescence, but the loss of its secondary structure as monitored by UV/CD occurs in a single step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 71 publications
5
72
0
3
Order By: Relevance
“…Using circular dichroism (CD) and a commercial HRP preparation similar to ours, Tsaprailis et al (1998) noted a single-step loss of HRP secondary structure between 1.2 and 2.7 M GdCl, with complete dissociation of the heme at 2.6 M GdCl and fluorescence changes in Trp117 above 4 M GdCl at pH 7.0. The unfolding half-time of native HRP in 6 M GdCl was 8.65 min.…”
Section: Unfolding Of Native and Pa-hrpsupporting
confidence: 51%
See 2 more Smart Citations
“…Using circular dichroism (CD) and a commercial HRP preparation similar to ours, Tsaprailis et al (1998) noted a single-step loss of HRP secondary structure between 1.2 and 2.7 M GdCl, with complete dissociation of the heme at 2.6 M GdCl and fluorescence changes in Trp117 above 4 M GdCl at pH 7.0. The unfolding half-time of native HRP in 6 M GdCl was 8.65 min.…”
Section: Unfolding Of Native and Pa-hrpsupporting
confidence: 51%
“…This difference could possibly arise from the in- troduction of a negative charge by phthalic anhydride modification close to one of the Ca 2+ binding sites. Tsaprailis et al (1998) observed that prior incubation with 2 mM EDTA for 18 h made HRP more prone to GdCl-induced denaturation and that HRP was greatly destabilized by EDTA combined with a reducing agent (DTT). Here, the reducing agent TCEP cleaves HRP's disulfide bridges in presence of GdCl, leading to unfolding and decreased activity.…”
Section: Unfolding Of Native and Pa-hrpmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies showed that active HRP is formed via at least two steps: folding of nascent polypeptide to apoenzyme, which is assisted by calcium, and its conversion to holoenzyme by binding hemin (29,31). We therefore examined the effect of CaCl 2 on folding of HRP in the present study.…”
Section: Overexpression Of Dsb Proteins Alleviates Growth Inhibitionmentioning
confidence: 98%
“…The insertion of an additional disulfide bond close to the distal Ca 2ϩ ion-binding site resulted in an apparent increase in the stability of the heme environment and active state of the protein. The particular significance of the Ca 2ϩ ions and disulfide bridges to protein stability has been underlined by a comparative study of HRPC and the class I peroxidase cytochrome c peroxidase in the presence of denaturants (44). The considerably lower kinetic stability found for cytochrome c peroxidase was attributed to the absence of these two stabilizing structural elements.…”
Section: Roles Of the Calcium Ions In Hrpcmentioning
confidence: 99%